Knowledge About Bullying by Young Adults With Special Educational Needs With or Without Disabilities (SEN/D) - González-Calatayud, Víctor; Roman-García, Marimar; Prendes-Espinosa, Paz (Frontiers in Psychology, 2021)
Bullying of people with Special Educational Needs with or without disabilities is a reality, being one of the most affected groups. This study presents the data obtained in a European Erasmus+ project in which 96 young people and adults with SEN/D from four countries participated: Ireland, Spain, Italy and Portugal. Firstly, a questionnaire was passed to see the general knowledge of these people in relation to bullying. Then a training programme was carried out and finally the questionnaire was passed again to see if the data improved. From the data it appears that people with SEN/D lack skills, knowledge and resources to deal with bullying. After the completion of the training programme the data obtained from the questionnaire improved in many respects. Sometimes people with SEN/D are not aware that they are suffering from this type of situation due to lack of knowledge, so it is necessary to continue implementing training programmes to help improve this situation.